2013
DOI: 10.7860/jcdr/2013/4707.2874
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension Amongst Adult Patients Attending Out Patient Department of Urban Health Training Centre, Department of Community Medicine, Era’s Lucknow Medical College and Hospital, Lucknow

Abstract: Background: Hypertension is the most common disorder which is encountered in outdoor patients. The existing data suggests that there is an increase in the prevalence of pre-hypertension and hypertension in India. The prevalence of hypertension will increase even further, unless broad and effective preventive measures are implemented. The main objective of this study was to find out the prevalence of hypertension amongst the adult outdoor patients of an urban health centre of Lucknow district. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
20
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 9 publications
6
20
2
Order By: Relevance
“…Above 60 year of age every second individual suffered from hypertension. Result of our study coincide with study done by Mahmood et al 24 who found prevalence of hypertension significantly higher among individuals aged between 41-50 years (49.0%) as compared to those aged between 30-40 years (7.4%). Similar result was found in another study done by Laxmaiah et al, risk of hypertension was nearly 2 and 5 times higher among 35-59 and ≥60 yr old men, respectively compared with 20-35 yr old in tribal population.…”
Section: Discussionsupporting
confidence: 81%
“…Above 60 year of age every second individual suffered from hypertension. Result of our study coincide with study done by Mahmood et al 24 who found prevalence of hypertension significantly higher among individuals aged between 41-50 years (49.0%) as compared to those aged between 30-40 years (7.4%). Similar result was found in another study done by Laxmaiah et al, risk of hypertension was nearly 2 and 5 times higher among 35-59 and ≥60 yr old men, respectively compared with 20-35 yr old in tribal population.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of hypertension was 24.4% and pre-hypertension was 29.3% in a study conducted by Syed Esam Mahmood et al among the adult outpatients of Lucknow. 1 In a study conducted among the adult tribal population of Kerala state, it was found that 37% were hypertensives. 2 In our study, it was found that the prevalence of hypertension was 41.3% and 20% among adult men and women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the outpatient consultations are with indigenous and private practitioners, where regular screening for hypertension is not practiced. 1 Hypertension has been identified as the leading risk factor for mortality and ranked third as the cause of 'disability adjusted life years. ' The prevalence of hypertension and its complications are increasing nowadays due to factors like economic development, changes in lifestyle, diet and increase in life expectancy.…”
mentioning
confidence: 99%
“…Changes of BP with age might be due to the changes in the vascular system [11]. Peculiar features of large and small arteries that occur with aging include endothelial dysfunction, vascular remodeling, inflammation, calcification, and increased stiffness [12].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of stage 1 and stage 2 HTN was higher in the older subjects. Changes of BP with age might be due to the changes in the vascular system [11,18].…”
Section: Discussionmentioning
confidence: 99%